Making Shakespeare : from stage to page - Stern, Tiffany (Accents on Shakespeare., 2004)
This gives a lively introduction to the major issues of the stage and print history of the plays, and discusses what a Shakespeare play actually is. This superb collection of new essays offers a uniq.